Potential for Ecotourism in Nepal - Ojha, Niranjan (Interdisciplinary Journal of Management and Social Sciences, 2020)
Ecotourism is a new approach in modern tourism. Sustainable tourism, green tourism, rural tourism, community-based tourism are the relative terms for ecotourism which have been emerged before 30 years. The potential of ecotourism as a strategy for sustainable development which was recognized during the Earth Summit in 1992 when sustainable tourism was considered as an environment friendly economic activity.Ecotourism is a burning issue and one of the fastest growing sectors in the world tourism industry. In Nepalese perspective tourism is in flux and gradually heading towards mass tourism. So it is the right time to implement the principles of ecotourism for its sustainability. Nepal Tourism Policy 2009 and Vision 2020 identify ecotourism as the key vehicle for sustainable tourism. Nepal government has been focusing it since long. Proper implementation of ecotourism principles can be very beneficial in Nepalese industry to achieve the desired goal.